Development of a dynamic model of a biomass boiler using Flownex - Bosch, Pierre (Department of Mechanical Engineering, 2025)
The textile, distillery, and pharmaceutical commercial enterprises are among a large group of industries requiring process steam in their production processes. The shift towards renewable energy sources is extended to industrial scale steam generators, whose designs need to allow flexibility in firing renewable and carbon neutral fuel sources such as biomass. The present work focusses on developing a dynamic model of a unique hybrid water-tube—fire-tube boiler. The numerical model has been developed using Flownex, a one-dimensional thermohydraulic simulation software with the aim of presenting credible insights into transient performance and controllability of the boiler of interest. This study develops stand-alone numerical models of the economiser, air heater, fire-tube evaporator, and water-cooled furnace as the four main heat exchangers in the boiler. Each heat exchanger is modelled sequentially using simplified analytical methods in Mathcad followed by detailed numerical implementations in Flownex. They are then verified against available maximum continuous rating (MCR) data before being integrated into a whole-boiler flow network. Limitations in availability of site data and availability of high-fidelity CFD furnace validation, meant implementing assumptions such as the inclusion of localised convection effects during calibration with the available site measurement data. The fine tuning of the model during calibration extended to fluid absorptivity and cooling air ratio parametric studies in search of the best calibration point which agreed reasonably well with site measurements from steady state test results. The impact of thermal inertia from the boiler's solid steel heat exchanging surfaces is demonstrated via a comparison of the results of uncontrolled transient runs between the realistic full inertia configuration and a low-inertia configuration of the Flownex model. The full inertia model captured the thermal mass of all the steel in the system including the finned tubes of the economiser, tubes of the air heater, furnace waterwall tubes, fire-tubes, solid steel staybars and evaporator shell. A key transient indicating parameter is the water-level inside of the evaporator. Much effort was therefore spent discretising the evaporator water volume to provide accurate level-tracking during transient simulations in the Flownex simulation environment. The transient operational scenarios investigated included a stepped steam demand profile and stepped fuel moisture profile with active boiler pressure and level control. The methodology and results establish a foundation for supplementary control optimisation investigations for future studies. Despite some data limitations for validated transient studies, this work presents a high fidelity controllable dynamic model of the hybrid boiler, which after validation can be used to emulate real world controllable boiler operations.